Kepemimpinan Kepala Madrasah dalam Meningkatkan Budaya Organisasi Kondusif di MTsN 3 Sijunjung - Mitra Turrohma; Suswati Hendriani (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research is to examine how the role of the madrasa head plays an important role in creating a good organizational culture at MTsN 3 Sijunjung. A good organizational culture is very important to create an effective and productive educational environment. This case study was carried out using a qualitative approach, and data was collected through observation, documentation, and in-depth interviews. Studies show that madrasa heads have a strategic role in building a good organizational culture by using leadership strategies such as effective communication, staff empowerment, and continuous professional development. It has been proven that inspirational and participative leadership can increase employee involvement and motivation and create a harmonious and collaborative work environment. This research shows how important it is for madrasa heads to establish a good organizational culture, which helps improve education in madrasas